2022
DOI: 10.1021/acsestengg.1c00457
|View full text |Cite
|
Sign up to set email alerts
|

Counterion Mobility in Ion-Exchange Membranes: Spatial Effect and Valency-Dependent Electrostatic Interaction

Abstract: Enhancing the selectivity of ion-exchange membranes (IEMs) is an important need for environmental separations but is hindered by insufficient understanding of the fundamental transport phenomena. Specifically, existing models do not adequately explain the order of magnitude disparity in diffusivities of mono-, di-, and trivalent ions within the membranes. In this study, a transport framework is presented to describe counterion migration mobility using an analytical expression based on firstprinciples. The two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 105 publications
1
51
0
Order By: Relevance
“…These electrostatic interactions impose friction-like losses on permeating ionic species, retarding their movement across the IEM and resulting in reduction of the effective mobilities. Our previous work showed that u m is related to , where A is an aggregated parameter of , permittivity, temperature, universal constants, and a conversion coefficient (Fan et al, 2022). Critically, u m decays exponentially with z 2 .…”
Section: Valence Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…These electrostatic interactions impose friction-like losses on permeating ionic species, retarding their movement across the IEM and resulting in reduction of the effective mobilities. Our previous work showed that u m is related to , where A is an aggregated parameter of , permittivity, temperature, universal constants, and a conversion coefficient (Fan et al, 2022). Critically, u m decays exponentially with z 2 .…”
Section: Valence Selectivitymentioning
confidence: 99%
“…( 4)). Our previous work indicated that absolute ion mobilities are affected by electrostatic interactions, with u m being reciprocally dependent on the exponential of and ε −2 , where ε is permittivity experienced by the permeating ions within the IEM matrix (Fan et al, 2022). Therefore, increasing the membrane fixed charge densities and reducing the dielectric of the local environment in the hydrated nanoscale channels can, in principle, exaggerate the retardation of species with higher |z|, with lower valency counterions impeded to smaller extents.…”
Section: Valence Selectivitymentioning
confidence: 99%
“…Similar to the uphill mass transfer of Na + in CEM DD, [Cl – ] in the feed surpasses the receiver after ≈2.0 h in the AEM experiments and continues to transport against the concentration gradient. As the electrochemical potential driving ion transport is depleted, a decreasing mass transfer rate is observed: 66% of the change in Cl – concentration is achieved in the initial 2 h and only 8% from 4.0 to 8.0 h. The kinetics of anion exchange is overall slower than that of CEM DD because the Selemion AMV has lower ion conductance compared to the CEM. , Meanwhile, co-ion Na + leaks across the AEM to the receiver chamber and accumulates to 0.731 ± 0.112 mM, which is negligible compared to [Cl – ]. The HCO 3 – exchanged to the feed chamber is 93.8 ± 1.3 mM, and 22.4 ± 1.3 mM NH 4 + permeates across the AEM to the feed chamber (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Fig. S3 in the Supplementary Material presents sorption coefficients, X i , for (details on the mechanisms of valence-selectivity can be found in literature) (Fan et al, 2022;Lu et al, 2011;Saracco, 1997;Saracco and Zanetti, 1994). Because the predominant orthophosphate species in fresh urine is H 2 PO 4 − , DD with the ASVN MIPM is expected to improve selectivity for H x PO 4 (3− x)− over SO 4 2− relative to the conventional AMV.…”
Section: Orthophosphate Fluxes Are Diminished By the Competing Anionsmentioning
confidence: 99%
“…More generally, both ion fluxes are significantly diminished with the MIPM relative to the conventional AEM (71.3 and 95.8% lower for J P and J S , respectively). The monovalent ion selective coating on the ASVN membrane is composed of highly crosslinked resin, which creates additional steric hindrance for permeating ions (Fan et al, 2022;Lu et al, 2011;Saracco, 1997;Saracco and Zanetti, 1994).…”
Section: Orthophosphate Fluxes Are Diminished By the Competing Anionsmentioning
confidence: 99%